Model of Base Saturation Flow to Improve Indonesia Highway Capacity Manual at Signalized Intersection - Irawati, Iin; Munawar, Achmad; Setiadji, Bagus Hario (Jurnal Teknik Sipil dan Perencanaan, 2023)
The intersection is a significant part of the urban traffic network. One of the problems of signalized intersections is the results of an analysis that do not match the field. For the analysis of signalized border crossings in 1997 Indonesia, the Indonesia Highway Capacity Manual, a product of the 1994 data processing, was used. Traffic conditions in 1994 were, of course, different from traffic conditions today. Given the significant changes related to traffic, such as increases in the number of vehicles, land use, behavior, road geometry, and technical complexity, the 1997 IHCM  needed to be improved according to the current situation. One quantity in IHCM is base saturation flow or So, which is an essential parameter in signalized intersection analysis. Base saturation flow (So) in 1997 IHCM   is 600 x We. After modeling and chi-variance test of ρ value ˂0.05 in the range 675 x We to 1000 x We^85, the result is So, which is the result of the queue length approximation field is 1000 x We.